STRATEGI PEMBERDAYAAN BADAN USAHA MILIK DESA (BUMDES) TERHADAP PENINGKATKAN PENDAPATAN MASYARAKAT DESA TEPOROMBUA KABUPATEN KONAWE SELATAN - Nur Abdul Husen; Zainuddin Saenong; La Tondi (Universitas Halu Oleo, 2021)
This study aims to obtain information about the BUMDes empowerment strategy to increase the income of the people of Teporombua village, Konawe Selatan district. This research was conducted with field research (field research) and used a qualitative descriptive approach, namely interviews with members of BUMDes and village communities totaling 20 people. The interviews were conducted in a relaxed nature, not complicated, the questions asked were not interrogating, but only to obtain the desired data to complete the writing in the research. The results show that the BUMDes empowerment strategy to increase the income of the people of Teporombua village is to create two types of business units where the strategy of empowering the business is by providing capital to the community, while the strategy for community empowerment is socializing BUMDes to villagers, and its institutional strategy by providing training. BUMDes members regarding the management and management of BUMDes.